Collaborative user interface design of a remote device control system - Toivanen, Miika (My University, 2024)
This thesis explores how the user interface of a remote device control system can be re-designed and re-implemented in collaboration with the users of the current sys- tem. First, a literature review is conducted to identify appropriate research methods for involving users in the design and implementation process. This is followed by exploring the evaluation methods that are used to collect numerical data about the current and the new user interface. The chosen methods for user involvement were focus groups and semi-structured interviews, and for evaluation methods System Usability Score and time-on-task were selected. The tools used to conduct the re- search are also introduced. The thesis then discussed the technical background and introduces more technical tools that are used. The re-design process is done in collaboration with the users by using the data collected from the users as a foundation for the design. Figma prototypes are used to facilitate iterative design refinement in order to validate assumptions. The thesis then briefly discussed the implementation phase and the limitations related to it. The current and the new user interface were compared against each other by using the selected evaluation methods. The new user interface was successful in improving both the SUS score and the time measured from time-on-task tasks. The average measured SUS score increased by 65%, transitioning from a grade of D to a grade of A+. Time spent on tasks was improved by 9%, although the change was smaller than anticipated.
Keywords: user interface design, remote device control system, human-computer interaction, UI, visual design, user-centered design